2018
DOI: 10.1108/lht-01-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Why is self-service technology (SST) unpopular? Extending the IS success model

Abstract: Purpose Self-service technology (SST) has become popular in many areas, but consumers from many countries still prefer human-provided services. Why is this so? The purpose of this paper is to understand the possible reasons by integrating two perspectives: personal characteristics marketing and the information systems success model (IS success model). Design/methodology/approach The authors propose an integrated model and conduct an empirical questionnaire survey which generates a total of 345 valid response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
1
12
0
2
Order By: Relevance
“…One should bear in mind that the design aspect of the SSTs would have a positive effect on satisfaction and service excellence for both business and leisure travelers. The positive effect of design on satisfaction in this research is in line with the previous studies [84]. Interestingly, convenience can only bring about satisfaction and service excellence for business travelers and not leisure travelers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…One should bear in mind that the design aspect of the SSTs would have a positive effect on satisfaction and service excellence for both business and leisure travelers. The positive effect of design on satisfaction in this research is in line with the previous studies [84]. Interestingly, convenience can only bring about satisfaction and service excellence for business travelers and not leisure travelers.…”
Section: Discussionsupporting
confidence: 91%
“…In the study of the usage behavior of SSTs in Taiwan airport, authors found that when SSTs design is visually appealing, passengers are more likely to be attracted to use them [83]. Design is one of the factors that determine the perceived satisfaction with SSTs [62,84]. This prompts the hypothesis that: Hypothesis 1e.…”
Section: Designmentioning
confidence: 99%
“…The researcher in [9] employed an extended IS success model to investigate the failure of self-service technology implementation. The author found that the individual technology anxiety and the need for the personal interaction became major factors affecting the technology acceptance.…”
Section: Related Workmentioning
confidence: 99%
“…Ulusal ve uluslararası literatür incelendiğinde Bilgi Sistemleri Başarı Modeli; çeşitli amaçlarla geliştirilen teknolojilerin benimsenmesi ve kullanımı üzerinde etkili olan faktörlerin tespiti için, farklı alanlarda sıklıkla araştırılmıştır. Bunlar; çevrimiçi öğrenme sistemleri (Alksasbeh vd., 2019;Isaac vd., 2019;Aldholay vd., 2018a;Seta vd., 2018;Efiloğlu Kurt, 2016;Mohammadi, 2015;Alharbi ve Drew, 2014), e-devlet uygulamaları (Sari vd., 2017;Stefanovic vd., 2016;Rana vd., 2015;), bankacılık sistemleri (Albashrawi ve Motiwalla, 2017, Jaafreh, 2017Tam ve Oliveira, 2016), bulut teknolojisi (Chiu vd., 2016), sosyal medya arama motorları kullanımı (Dang vd., 2018); sanal seyahat toplulukları (Gao vd., 2014), dijital kütüphane sistemleri (Alzahrani vd., 2017), e-ticaret siteleri (Hsu vd., 2014), hemşire bilgi sistemi (Lin, 2017), self-servis teknolojilerin benimsenmesi (Lian, 2018), farklı alanlarda geliştirilmiş mobil uygulamaların kullanımıdır (Wang vd., 2019;Lin ve Chang, 2018;Özata & Er, 2015). Bu kapsamda Al-Kofahi vd.…”
Section: Sayfa | 490unclassified
“…Kullanıcılar mobil uygulama sistem kalitesini, istediği seviyede algılarsa, söz konusu uygulamaya karşı yüksek memnuniyet düzeyi gösterme eğiliminde olacaktır (Albashrawi ve Motiwalla, 2017: 3) ve bu sonuç mobil uygulamalar (Özata ve Er, 2015;Jaafreh, 2017;Lin ve Chang, 2018;Wang vd., 2019), sanal seyahat siteleri (Gao vd., 2014), self-service teknolojiler (Lian, 2018); bilgi yönetim sistemi (Wu ve Wang, 2006), dijital kütüphaneler (Alzahrani vd., 2017) gibi farklı sektörlerde uygulanan çalışmalarca da desteklenmektedir. Bu kapsamda H2 hipotezi; H2: Sistem kalitesi ile kullanıcı memnuniyeti arasında anlamlı bir ilişki vardır.…”
Section: Sistem Kalitesiunclassified